Cross species transmission of pseudorabies virus leads to human encephalitis and visual impairment: A case report - Huang, Hui; Wang, Na; Ai, Zhi-Bing; Chen, Jun; Huang, Wei; Bao, Yi (Frontiers in Neurology, 2022)
Pseudorabies virus (PRV) is a common pig infectious disease. There have been few reports of PRV infection in humans. The patient in this article had acute onset, which was manifested by fever, epilepsy, disturbance of consciousness, and other symptoms. The disease progressed rapidly and worsened in a short time so the ventilator had to be used to assist breathing. In the later stage of treatment, serious visual impairment also occurred. Pseudorabies virus was found in cerebrospinal fluid by second-generation gene sequencing (NGS). This indicates that the pseudorabies virus can spread across species, leading to human encephalitis and severe visual impairment. Therefore, attention should be paid to this disease, active prevention, and early detection are helpful to improve the treatment effect.